Computational tracing tool to extract potential pattern of computer literacy among e-Books users / Mohd Talmizie Amron, Norizan Mohamad and Azlin Dahlan - Amron, Mohd Talmizie; Mohamad, Norizan; Dahlan, Azlin (2013)
Nowadays being a computer literate is necessary. Persons with sufficient computer literacy skills should possess both the knowledge and ability to use computers and the associated technology efficiently. In educational sector, the state government is investing considerably in promoting computer literacy among the pupils through the supply of electronic books (e-book). It is a significant commitment towards achieving a fully developed nation through the Vision 2020 plan. One of the important agendas is to prepare the citizens to be a knowledgeable workforce. It is therefore crucial that the pupils be equipped with the necessary computer skills in response to this workforce requirement. However, the pupils in schools vary in their capacity and abilities in learning to use computer technologies. A performance indicator of their computer literacy skills should be able to indicate their current computer literacy level. Hence, to ensure that the government’s end-results are achievable and meet the workforce requirement, the computer literacy of the pupils should be measured periodically. How to best measure the computer literacy skills among the pupils remains a question. The objectives of this study are to explore the possibility of using suitable tracing tool for capturing computing activities, to develop automated tracing tool to analyze the log file and to identify the patterns of computer literacy skills among e-book users. This research is using the PCAgent tool, to provide a log file for the tracing tool. Each user’s action was recorded and the completion time was also captured. Using the tracing tool, the accuracy percentage for all the tasks was calculated as well as the completion or response time. In this research, we found out that response time factor need to be explored further since it gave a slightly contradicting result against the accuracy factor. Hence, in this research, only the accuracy factor was used as a classifier for the expertise classification task.